Echocardiographic findings in children with Tetralogy of Fallot
Background and Aims: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart disease in children. The aim of this study was to identify various cardiac defects associated with TOF by transthoracic echocardiography. Methods: All children presenting to Shahid Gangalal National Heart Centre, with the diagnosis of TOF from 2014 to 2015 were included in the study. Echocardiograpic reports of all eighty eight children were reviewed. Results: The mean age of presentation was 3.5